ChemInform Abstract: Synthesis of Phenylalkyl‐Substituted Polyhydroxypiperidines as Potent Inhibitors for α‐L‐Fucosidase. Issue 16 (22nd April 2014) - Toyooka, Naoki; et al., et al.
Abstract Key intermediate (III) is converted into homologues (V) and (VIII) either by Lemieux—Johnson oxidation and subsequent Wittig reaction or in one step by Grubb metathesis, respectively.